Leaving the day behind: endovascular therapy beyond 24 h in acute stroke of the anterior and posterior circulation. (May 2022) - Purrucker, Jan C.; Ringleb, Peter A.; Seker, Fatih; Potreck, Arne; Nagel, Simon; Schönenberger, Silvia; Berberich, Anne; Neuberger, Ulf; Möhlenbruch, Markus; Weyland, Charlotte
Background: There is little evidence of endovascular therapy (EVT) being performed in acute ischemic stroke beyond 24 h, and that evidence is limited to anterior circulation stroke. Objective: To extend evidence of efficacy and safety of EVT after more than 24 h in both anterior and posterior circulation stroke. Methods: Local, prospectively collected registries were screened for patients with acute ischemic stroke and large-vessel occlusion who had received either EVT > 24 h after last-seen-well but <24 h after symptom recognition (EVT>24LSW ) or EVT > 24 h since first (definitive) symptom recognition (EVT>24DEF ). Patients treated <24 h served as a group for comparison. Favorable outcome was defined as modified Rankin scale (mRS) 0–2 or return to prestroke mRS at 3 months. Results: Between January 2014 and August 2021, N = 2347 were treated with EVT at our comprehensive stroke center, of whom n = 43 met the inclusion criteria (EVT>24LSW, n = 16, EVT>24DEF, n = 27). EVT>24LSW patients were treated at a median of 28.7 h [interquartile range (IQR) = 27.3–32.8] after last-seen-well and 7.3 h (IQR = 2.8–14.3) after symptom recognition; EVT>24DEF patients were treated 52.5 h (IQR = 26.5–94.2) after first symptoms. Favorable outcome was achieved by 23.3% (10/43) in the EVT > 24 compared with 39.4% (886/2250) in the EVT < 24 group ( p = 0.04). Bleeding rates were similar across groups. Mortality was also similar [EVT > 24, 27.9% (12/43) versus EVT < 24, 25.7% (584/2264), p = 0.727; posterior circulation, EVT > 24, 41.7% (5/12) versus EVT < 24, 36.5% (92/252) p = 0.764]. Conclusion: In selected patients, EVT seems effective and safe beyond 24 h for both anterior and posterior circulation stroke.